The Existence of Hajj Tale as a Cultural Identity in Tigo Luhah Semurup, Kerinci Regency - Supian Supian; Denny Defrianti; Fatonah (Proceeding International Conference on Malay Identity, 2020)
This research is a descriptive qualitative research with a social theory approach. The purpose of this research is to find out the existence and application of the tale haji tradition as a cultural identity in Tigo Luhah Semurup, Kerinci Regency. This tradition has been carried out from generation to generation until now, this is done as a form of gratitude to Allah SWT as the chosen people to worship in the holy land of Mecca. The lengthy process and journey to the holy land makes the poems sung full of meaning containing prayers and hopes to Allah SWT so that prospective pilgrims who will depart can leave their hometowns in peace and be given safety and smoothness in carrying out the pilgrimage, while for the families left behind are still given consolation and support to await the arrival of the families who depart for the holy land. This tradition produces a sense of togetherness, the spirit of mutual cooperation, sincerity, affection, kinship and cohesiveness among the local community. The conclusion from this research is that the implementation of the tale haji tradition is a sacred form as a cultural identity in Tigo Luhah Semurup, until now the community believes in maintaining and preserve it as a legacy of hereditary traditions. the activity of the haji butale tradition gave birth to noble values ??as strengthening and bonding values ??for family relations, togetherness, mutual cooperation, sincerity, sincerity and affection in the Tigo Luhah Semurup community, Kerinci district.Keywords: Hajj Tale, Tradition, Cultural Identity